BERTAHAN DI TENGAH KRISIS: PENDIRIAN UNIVERSITAS MUSLIM INDONESIA (UMI) MAKASSAR, 1945-1965 - Anna Asriani Muchlis (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2017)
The idea to establish an Islamic university in Makassar came from Prof. Huzairin, a prominent Islamic intelectual in Jakarta and one of the leaders of Universitas Islam Djakarta (UID). The idea was followed by Naziruddin Rahmat who was a staff of the Ministry of Religion who was assigned to Makassar by establishing Universitas Muslim Indonesia (UMI). With the support of South Sulawesi community leaders in Makassar the process which started in 1952 finally led to the establishment of UMI on June 23rd 1954. The following year the Waqaf Foundation of UMI was established. However, Mochtar Lintang who was entrusted to become the first President of UMI could not finish his tenure due to his involvement in the PRRI/ Permesta rebelion. This period constituted UMI’s first crisis. The second president, Abdurrahman Shihab, faced challenges from students when he tried to reorganize departments within the university and merged them with similardepartments in the National Islamic Religious Institute (IAIN). This was UMI’s second crisis. Despite all these challenges, UMI could thrive and develop beyond past difficulties.